Paracetamol induced Steven-Johnson syndrome: A rare case report - Rajput, Rajan (Contemp Clin Dent, 2015)
In the contemporary era, use of drugs is the dominant paradigm of health care. The most quotidian drug used for fever and pain is paracetamol. Although adverse reactions to paracetamol in India are rare, at times they can cause life-threatening situations. Stevens-Johnson syndrome (SJS) is one such potentially lethal adverse drug reaction. The most reported cases of analgesic-induced SJS were due to oxicams or propionic acid derivatives. There are very few detailed reports of SJS due to the use of paracetamol. We report a case of SJS, which occurred due to the use of paracetamol. The clinical features of this condition and multidisciplinary management of the patient are described in brief.